Integrating Character Education into STEM-Based Chemistry Learning Through Interactive Digital Media - Feby Indayani (Information Technology Education Journal, 2025)
This study examines the integration of character education into STEM-based chemistry learning enhanced by interactive digital media in secondary schools in Mamuju, West Sulawesi. The research investigates how four instructional components STEM Implementation, Character Education Integration, Teacher Competence, and School Support collectively influence Character Outcomes and Chemistry Achievement when delivered through digital interactive platforms. Using a quantitative design, data were collected from 300 students and analyzed through descriptive statistics, correlation testing, and multiple regression models. The results show that Character Education Integration remains the strongest predictor of Character Outcomes, demonstrating that explicit value-based instructional strategies significantly shape students’ ethical behavior, responsibility, and collaboration. STEM Implementation also contributes substantially to both outcomes, particularly when supported by interactive digital tools such as virtual laboratories, simulations, and digital modeling environments that facilitate inquiry, real-time feedback, and authentic scientific engagement. Teacher Competence is identified as the primary determinant of Chemistry Achievement, emphasizing the need for strong pedagogical content knowledge and digital proficiency to optimize the use of interactive media in STEM-based chemistry instruction. Although School Support shows the smallest effect, it remains a significant enabling factor by providing technological infrastructure and administrative backing necessary for consistent digital-based learning. Overall, the findings indicate that integrating character education within digital-supported STEM chemistry learning produces synergistic benefits for both cognitive and affective domains. This study underscores the importance of combining STEM pedagogy, character-focused instruction, and interactive digital media to enhance student learning experiences and inform policy and instructional development in emerging educational contexts.